2018
DOI: 10.1016/j.cnp.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of neurophysiologic changes during surgical treatment of carotid stenosis using signal analysis

Abstract: HighlightsSignal processing of the SSEP obtained during treatment of carotid artery disease.Differences between control and unoperated and operated sides.Differences between treatment with open or endovascular approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…1 In a previous report, we described a new method of analyzing the SSEP (and any neurophysiological waveform). 2 We showed that, in cases in which there were no neurological changes during carotid surgery (open or endovascular) and no changes in the SSEP according to the classical alert criteria, the new technique showed differences between stenting and endarterectomy and differences between patients undergoing lumbar spine surgery and those with symptomatic carotid stenosis requiring surgery. In particular, we measured the velocity of the upswing of the N20.…”
mentioning
confidence: 83%
“…1 In a previous report, we described a new method of analyzing the SSEP (and any neurophysiological waveform). 2 We showed that, in cases in which there were no neurological changes during carotid surgery (open or endovascular) and no changes in the SSEP according to the classical alert criteria, the new technique showed differences between stenting and endarterectomy and differences between patients undergoing lumbar spine surgery and those with symptomatic carotid stenosis requiring surgery. In particular, we measured the velocity of the upswing of the N20.…”
mentioning
confidence: 83%